2022
DOI: 10.1097/md.0000000000028884
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on outpatients of internal medicine and pediatrics

Abstract: This study analyzed the changes in the number of outpatients and disease presentation during the entirety of 2020, the period of COVID-19 pandemic.The average annual number of outpatient visits between 2017 and 2019 (before COVID-19) and the total number of outpatient visits in 2020 (COVID-19 period) were compared. Diagnostic codes were identified during 2 periods to analyze changes in the number of outpatient visits according to disease and month.The average annual number of outpatient visits was 47,105 befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…But the suppressed health-seeking demand from non-COVID-19 diseases was released after the lockdown period, forming a drastic post-lockdown surge. This fall-rebound pattern was also reported by a study from Israel in that noted a decrease in hospital admissions for myocardial infarction was observed during the early stage of the epidemic, as well as a rebounding increase upon the receding end of the first wave of the epidemic ( 11 ) Another study from Korea also showed that the number of outpatient visits in internal medicine decreased during the COVID-19 pandemic and tended to rebound during the second half of the year ( 19 ) Subsequently, medical visits gradually fell back to the baseline level of prior years, reflecting the normalization of health-seeking demand during the post-SARS-CoV-2 period in China.…”
Section: Discussionsupporting
confidence: 68%
“…But the suppressed health-seeking demand from non-COVID-19 diseases was released after the lockdown period, forming a drastic post-lockdown surge. This fall-rebound pattern was also reported by a study from Israel in that noted a decrease in hospital admissions for myocardial infarction was observed during the early stage of the epidemic, as well as a rebounding increase upon the receding end of the first wave of the epidemic ( 11 ) Another study from Korea also showed that the number of outpatient visits in internal medicine decreased during the COVID-19 pandemic and tended to rebound during the second half of the year ( 19 ) Subsequently, medical visits gradually fell back to the baseline level of prior years, reflecting the normalization of health-seeking demand during the post-SARS-CoV-2 period in China.…”
Section: Discussionsupporting
confidence: 68%
“…The highest percentage change was related to the number of outpatients, representing a considerable decline. Previous studies demonstrated that the average annual number of outpatient visits [21][22][23][24][25][26], inpatient admission, MRI services and surgical decreased during COVID-19 [27][28][29]. Hung et al, reported with the rise in inpatients, the…”
Section: Discussionmentioning
confidence: 99%
“…The main reason is that many private hospitals with insufficient manpower and resources were forced to shut down in order to prevent cross-infection during the epidemic, resulting in a significant decrease in the number of admissions and surgeries and revenues. [32][33][34] This provides evidence that COVID-19 caused great damage to the hospital system, and it was also confirmed by Jalilian et al, [31] King et al, [35] Byun et al, [36] and He et al [37] Similarly, Chen et al [38] argued that the revenue of public hospitals dropped dramatically during COVID-19, but recovered after COVID-19. In U.S. hospitals, operating margins decreased during the first 6 quarters of the COVID-19 crisis.…”
Section: Discussionmentioning
confidence: 68%